The Affinity of Elongated Membrane-Tethered Ligands Determines Potency of T Cell Receptor Triggering - Chen, Bing-Mae; Al-Aghbar, Mohammad Ameen; Lee, Chien-Hsin; Chang, Tien-Ching; Su, Yu-Cheng; Li, Ya-Chen; Chang, Shih-En; Chen, Chin-Chuan; Chung, Tsai-Hua; Liao, Yuan-Chun; Lee, Chau-Hwang; Roffler, Steve R. (Frontiers in Immunology, 2017)
T lymphocytes are important mediators of adoptive immunity but the mechanism of T cell receptor (TCR) triggering remains uncertain. The interspatial distance between engaged T cells and antigen-presenting cells (APCs) is believed to be important for topological rearrangement of membrane tyrosine phosphatases and initiation of TCR signaling. We investigated the relationship between ligand topology and affinity by generating a series of artificial APCs that express membrane tethered anti-CD3 scFv with different affinities (OKT3, BC3, and 2C11) in addition to recombinant class I and II pMHC molecules. The dimensions of membrane-tethered anti-CD3 and pMHC molecules were progressively increased by insertion of different extracellular domains. In agreement with previous studies, elongation of pMHC molecules or low affinity anti-CD3 scFv caused progressive loss of T cell activation. However, elongation of high affinity ligands (BC3 and OKT3 scFv) did not abolish TCR phosphorylation and T cell activation. Mutation of key amino acids in OKT3 to reduce binding affinity to CD3 resulted in restoration of topological dependence on T cell activation. Our results show that high affinity TCR ligands can effectively induce TCR triggering even at large interspatial distances between T cells and APCs.